El tractament de les formes nominals 'invariables' quant a nombre - Lloret, Maria Rosa (Caplletra. Revista Internacional de Filologia, 1995)
The starting claim of this paper is that it is not accidental that in Catalan, as in Spanish, invariable nominals regarding number end in the same form as the regular plural marker, i.e., s, and thus any analysis willing to explain these words has to take this fact into account. Under this assumption, different proposals are evaluated: the existence of a `zero'-plural morph, the blocking of s (plural marker)-insertion, the deletion of s-plural marker, the ambimorphic interpretation of -s+s, the unspecified blocking of one of the two ss, and the deletion of the s-stem. The latter analysis is favoured, except for compounds whose second element is already plural, in which case the ambimorphic analysis is preferred.